Yangonin Blocks Tumor Necrosis Factor-α-Induced Nuclear Factor-κB-Dependent Transcription by Inhibiting the Transactivation Potential of the RelA/p65 Subunit - Juan Ma; He Liang; Hong Ri Jin; Nguyen Tien Dat; Shan Yu Zhang; Ying Zi Jiang; Ji Xing Nan; Donghao Li; Xue Wu; Jung Joon Lee; Xuejun Jin (Elsevier, 2012)
The nuclear factor-κB (NF-κB) transcription factors control many physiological processes including inflammation, immunity, and apoptosis. In our search for NF-κB inhibitors from natural resources, we identified yangonin from Piper methysticum as an inhibitor of NF-κB activation. In the present study, we demonstrate that yangonin potently inhibits NF-κB activation through suppression of the transcriptional activity of the RelA/p65 subunit of NF-κB. This compound significantly inhibited the induced expression of the NF-κB-reporter gene. However, this compound did not interfere with tumor necrosis factor-α (TNF-α)-induced inhibitor of κBα (IκBα) degradation, p65 nuclear translocation, and DNA-binding activity of NF-κB. Further analysis revealed that yangonin inhibited not only the induced NF-κB activation by overexpression of RelA/p65, but also transactivation activity of RelA/p65. Moreover, yangonin did not inhibit TNF-α-induced activation of p38, but it significantly impaired activation of extracellular signal-regulated kinase 1/2 and stress-activated protein kinase/c-Jun NH2-terminal kinase. We also demonstrated that pretreatment of cells with this compound prevented TNF-α-induced expression of NF-κB target genes, such as interleukin 6, interleukin 8, monocyte chemotactic protein 1, cyclooxygenase-2 and inducible nitric oxide. Taken together, yangonin could be a valuable candidate for the intervention of NF-κB-dependent pathological conditions such as inflammation. Keywords:: yangonin, nuclear factor-κB (NF-κB), RelA/p65, transactivation, inflammation